ACQUISITION AND PEDAGOGY OF THE ARABIC EMPHATIC CONSONANTS (Romano-arabica, 2025)
English learners of Arabic struggle with acquiring Arabic emphatic consonants (Odisho, 2005), such as [ṣ], [ṭ], [ḍ], which are alveolar consonants marked by pharyngealization or uvularization as secondary articulation (Herzallah, 1990, Zuwaideh, 1999). Pedagogical research suggests that the pronunciation of these second language (L2) sounds can improve when teaching involves various classroom activities, training sessions, and feedback (Celce-Murcia and Goodwin 1996). However, it is unclear which specific types of activities (e.g., controlled versus communicative practice activities) are most effective for improving the perception and production of L2 Arabic emphatic sounds. Four tasks (articulatory, controlled, guided, and communicative activities) were prepared to study L2 learners’ acquisition of Arabic emphatics, followed by perception and production tests to monitor the learners’ progress. The results suggest that articulatory and controlled activities are more effective at improving learners’ perceptions, while guided and communicative activities are more effective at enhancing learners’ pronunciation. The results also show that different learners made progress after some training sessions, suggesting that diversifying the types of activities is crucial for learners with different learning styles and pace of convergence with native-like pronunciation.
Keywords: L2 acquisition; Arabic; emphatic consonants; controlled and communicative practice activities